Le Cyberspace and Cultural Hybridization - MBOMA MASAMBAY, Blaise; BULE WIDI, Christian (Revue Internationale du Chercheur, 2025)
Abstract As a virtual space for exchange and communication, cyberspace fosters cultural hybridization by facilitating the encounter and fusion of cultures. Thanks to the Internet, cultural identities are no longer fixed but evolve under the influence of digital interactions. Social networks, forums, and creative platforms enable the rapid dissemination of traditions, ideas, and lifestyles, giving rise to new forms of cultural expression. Cultural hybridization in cyberspace is particularly evident in music, fashion, language, and artistic practices. Geographical boundaries fade, leading to a blending of local and global cultures. This phenomenon can enrich cultural diversity by encouraging innovation and intercultural dialogue, but it also raises concerns about standardization and the hegemony of dominant cultures. Thus, while cyberspace serves as a powerful vehicle for cultural hybridization, it remains shaped by issues of power and representation. This article analyzes how cyberspace promotes cultural hybridization by facilitating interactions between different identities and influences. It explores the impact of new technologies on cultural dynamics and identity construction.